Metode Deteksi ‘Potential Security Threats’ Pada ADS-B Data dengan Memonitor EM Emisi Radiasi pada Jaringan Ethernet - Reza Septiawan; I Made Astawa; Arief Rufiyanto; Tahar Agastani (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
Precision, Navigation, and Timing (PNT) system based on Global Navigation Satellite System (GNSS) becomes significant in the air traffic management, especially in the use of Automatic Dependent Surveillance Broadcast system (ADS-B) for air traffic monitoring. Therefore the integrity of GNSS is significant to provide a reliable data necessary for ADS-B. GNSS Interference due to intentional or unintentional surrounding signal source may decrease the integrity of GNSS signal and therefore may result in the in-accurate position data of ADS-B message. ADS-B message itself is also vulnerable from potential security threats in their network. This paper proposed a methodology to detect potential security threats of ADS-B network system for both GNSS signal and ADS-B data by measuring and monitoring the electromagnetic radiated emission from ethernet cable IPv4 Cat5.